Towards Metabolomic-Based Precision Approaches for Classifying and Treating Heart Failure - Hahn, Virginia S.; Selvaraj, Senthil; Sharma, Kavita; Shah, Svati H. (JACC. Basic to translational science, 2024)
[Display omitted] •Patients with HF have impaired cardiac and systemic metabolism, and novel therapies to target metabolism are needed. Myocardial and peripheral metabolomics offer comprehensive measurement of small molecule metabolites in biological samples.•Several studies have highlighted the abnormalities in metabolomic profiles of patients with HF with preserved or reduced EF, both from peripheral blood and myocardial tissue. In this review, we synthesize the published reports on the metabolomics of HF and propose future directions.•Future studies are warranted to improve our understanding of single cell metabolomics, cardiac-specific metabolomics, flux through metabolic pathways, subgroup differences in metabolomic profiles, and response to pharmacologic and nonpharmacologic therapies. Both heart failure and cardiometabolic disease are on the rise, and abnormal cardiac and peripheral metabolism are central to the syndrome of heart failure. Advances in metabolomic profiling have improved our understanding of the heart’s metabolic flexibility in patients with and without heart failure. Prior studies have noted patients with heart failure display metabolomic profiles associated with marked abnormalities in the metabolism of fatty acids, branched-chain amino acids, ketones, and glucose compared with control subjects. Metabolomics can highlight specific pathways that are dysregulated; however, other metabolites beyond those related to fuel metabolism may also play a role in precision-medicine approaches. Novel approaches include metabolic flux studies, spatial and single-cell analysis, serial monitoring of treatment response, and integration with other -omics data. The goal of these innovative approaches should be to harness metabolomic technologies to affect precision care for patients with heart failure.